The Identification of Argumentation Reasoning in Learning Interpretation in Pondok Pesantren in Kalimantan Selatan - Basir, Abd.; Barni, Mahyuddin; Wahyuddin,; Mizani, Hilmi; Ilmi, Fajrul (International Journal of Psychosocial Rehabilitation, 2020)
The method of interpreting the holy book of the Qur'an carried out by each boarding school has a variety of interpretation models. This is inseparable from the influence of the educational background of the previous pesantren teachers. This influence is also believed to occur in several Islamic boarding schools in the province of South Kalimantan. For this reason, this study aimed to understand the interpretation model of the Quran carried out by a number of pesantren there. To obtain needed data, qualitative method research has been successfully carried out in several Islamic boarding schools. Then the results can be concluded that the interpretation model that is carried out in the South Kalimantan Islamic boarding school including; First, teachers and scholars interpret the Qur'an and other books to the students and their students are inseparable from the model or method of reasoning argumentation. Second, to give an explanation to the students, then they refer to the trusted commentaries. Third, the system and learning content of the books that are referred to are inseparable from the educational background taken by the teachers, both formal and non-formal education. So this finding is believed to not be able to be used as a full benchmark, therefore further studies can be done so that the understanding of the system and methods of our interpretation of holiness in education in pesantren can be increased to be more extensive and comprehensive.